Heterogeneous hydrochar-based catalysts for biodiesel production - Muhammad Aliyu; Rashid, Umer; Wan Ab Karim Ghani, Wan Azlina; Mohd Salleh, Mohamad Amran; Hazmi, Balkis; Garba Shitu, Ibrahim; Salisu, Ali (Springer, 2024)
The potential of heterogeneous hydrochar-based catalysts as a desirable technology for biodiesel production is highlighted in this book chapter. These hydrochar-based catalysts have renewable features, are cost-effective, and have efficient catalytic properties, making them an excellent choice in the field due to their high carbon content and unique physicochemical features. This chapter aims to provide a comprehensive review of the feedstock of hydrochar from different biomass sources including agricultural waste, food waste, and forestry waste. The hydrochar production technologies and factors affecting the properties of hydrochar during production were also discussed. The catalytic performance to produce biodiesel can be considerably improved by the development of types of heterogeneous hydrochar-based catalysts via introducing active species such as metal nanoparticles or acid- or base-functional groups onto the hydrochar surface, and the parameters that influence biodiesel yield and selectivity during biodiesel production utilizing heterogeneous hydrochar-based catalysts were discussed. The multifaceted nature of hydrochar, combined with its renewable origin and distinctive physicochemical properties, positions it as a valuable resource for advancing sustainable and efficient catalytic processes. Finally, this chapter advances knowledge on heterogeneous hydrochar-based catalysts and encourages further research in this promising area while outlining current research and future directions.